Influence of layer charge on swelling of smectites - Laird, David A. (Applied clay science, 2006)
Six separate processes control the swelling of smectites saturated with alkali and alkaline earth cations in aqueous systems. The basic mechanism and forces controlling each of the processes are different. Crystalline swelling occurs between smectite layers within quasicrystals and involves the intercalation of zero to four discrete layers of water molecules. A balance between strong electrostatic-attraction and hydration-repulsion forces controls crystalline swelling. The extent of crystalline swelling decreases with increasing layer charge. Double-layer swelling occurs between quasicrystals. An electrostatic repulsion force develops when the positively charged diffuse portions of double layers from two quasicrystals overlap in an aqueous suspension. Layer charge has little or no direct effect on double-layer swelling. The break up and formation of quasicrystals is a dynamic process that controls the average size of quasicrystals in an aqueous smectite suspension. As layer charge increases, quasicrystals tend to become larger and more stable. In smectite suspensions with more than one type of exchangeable cation, the cations can demix (e.g., Na and Ca may be segregated in different interlayer regions) due to a complex feed-back between cation exchange selectivity and crystalline swelling. Demixing influences the breakup and formation of quasicrystals because quasicrystals preferentially cleave along interlayers dominated by alkali cations. Increasing layer charge increases selectivity for alkaline earth cations relative to Na or Li, and hence reduces the breakup of quasicrystals. Co-volume swelling is an entropy driven process caused by restrictions on the rotational freedom of suspended quasicrystals. Brownian swelling is also an entropy driven process resulting from random thermal motion of suspended colloids. There is no reason to believe that layer charge directly influences either co-volume or Brownian swelling. Macroscopic measures of swelling (e.g., change in total volume or water content) necessarily measure the combined effect of all swelling processes occurring within the system.